المسؤولية الجنائية عن التحجير على المرأة في النكاح في النظام السعودي: دراسة تأصيلية - أبو عامر، هالة طالب محمود (جامعة قاصدي مرباح - ورقلة, 2018)
تهدف هذه الدراسة إلى بيان المسؤولية الجنائية عن التحجير على المرأة في النكاح ويقصد به: إجبار المرأة على الزواج ممن لا تقبل به، ومنعها من الزواج من الكفؤ الذي رضيت به زوجا، كما تتناول الدراسة أسباب التحجير على المرأة في النكاح وصوره المختلفة، وتوضح الدراسة حكم التحجير على المرأة في النكاح بصوره المختلفة في الشريعة الإسلامية، وفي النهاية تختتم الدراسة ببيان العقوبة المترتبة على التحجير على المرأة في النكاح في النظام السعودي، إضافة إلى خاتمة تتضمن عددا من النتائج والتوصيات. This study aims to explain the criminal responsibility for the quarrying of women in marriage, which means: "forcing a woman to marry who she does not accept, and preventing her from marrying the one who she wants as her husband." The study also discusses the reasons for the quarrying of women in marriage and its various forms. And it identifies the rule of the quarrying of women in marrige in the Islamic law, in addition to the decisions issued by the Council of Senior Scholars in the Kingdom, and generalizations related to it in the Saudi system. Finally, the study ends with a statement of the penalty of the quarrying of women in marriage in the Saudi system, in addition to a conclusion with a number of results and recommendations.
Keywords: الفقه الإسلامي -- الشريعة الإسلامية -- حقوق المرأة -- المسؤولية الجنائية -- القانون السعودي